THE IMPORTANCE OF THE NATIONAL CERT INSTITUTION FOR THE REPUBLIC OF SERBIA - Milica Lesanovic (Pravo)
The National CERT is the institution responsible for coordinating, preventing, and protecting against current security risks in the information and communication systems of operators at the national level. This article explores the mechanisms of protection, prevention, and response to security threats, emphasizing the role and importance of the CERT institution for the Republic of Serbia, the application of the Law on Information Security, and the raising of public awareness about information security. Various research methods have been applied, including the method of concretization, the combined method of analysis and synthesis, the inductive-deductive method, the comparative method, and the statistical method. The Law on Information Security regulates protective measures against security risks in information and communication systems, defines the responsibilities of legal entities in managing and using such systems, and determines the competent authorities for implementing those measures. Through supervision, control, and recordkeeping of all security threats in the Republic of Serbia, the National CERT enables proactive engagement by competent institutions, thereby enhancing the level of national security and Serbia’s position on the global stage.